An Interpretive Phenomenological Analysis exploring the experiences of language needs and Special Educational Needs and Disabilities (SEND) for secondary school teachers of English - Doherty, L (2023)
Government policy and publications have reiterated the message that all teachers should be teachers of Special Educational Needs and Disabilities (SEND) and meet the varying and diverse needs of all learners within a mainstream classroom (HM Government 2022a; 2022b). Language needs, a feature of a communication and interaction difficulty, is one area of SEND. Within the secondary school context, these difficulties have received little research attention and focus. This research with secondary school teachers of English (N=5) utilised semi-structured interviews and vignettes which provide written case study descriptions of how language needs may present in the classroom (Starling et al., 2011; Ramsey, 2015). Interpretative Phenomenological Analysis (IPA) was used to explore participants’ experiences. IPA is a qualitative methodology in which the central tenets focus on phenomenology (experience), hermeneutics (interpretation) and idiography (individual, nomothetic data) (Smith et al., 2022). Four group experiential themes were identified which depicted participants’ experiences of being a teacher and supporting language needs and SEND; Expertise; Interactions; Feeling Challenged; and Interpretation. How participants each related to these individual constructs varied and similarities (convergence) and differences (divergence) in their individual experiences were noted. The research provides a descriptive and interpretive account of the experiences of participants when teaching and supporting students with SEND and language needs. Situating these experiences within an ecological framework of the classroom, appreciates the contextualised experience of being a teacher and the interactions between students, other professionals, systems and structures and the emotive elements that accompanies this experience. Continued and renewed focus and awareness of the presentation of language needs in the secondary context remains pertinent as some teachers felt that they lacked expertise and confidence in this area. Educational Psychology as a profession may be unique in its contribution when supporting schools to consider holistic and ecological influences on the presentation of SEND and support the problem-solving capacity of the school workforce, particularly in an educational context where access to specialist services is hindered due to scarcity of resources.